CHARACTERISTICS OF INTERACTIVE LEARNING IN EDUCATION - S. Nurmanova (Web of Journals Publishing, 2024)
The article discusses the peculiarities of interactive and traditional teaching in education.
Keywords: Modernization, pedagogy, cooperation, innovative education, Interactive methods